The Validity of the Malaysian Teachers’ Global Competency Level Instrument Using Cohen Kappa, Content Validity Ratio and Content Validity Index Analyses - Ibrahim, Siti Nurul Aqiedah; Mohd Matore, Mohd Effendi Ewan (PT Mattawang Mediatama Solution, 2025)
Highly competent teachers are vital in developing globally competent individuals. There is a lack of empirical evidence supporting the validity aspect of the Malaysian Teachers' Global Competency Level Instrument. This study aims to evaluate face and content validity. A survey research design with a quantitative approach was conducted. It involves two experts for face validity and eight experts for content validity using purposive sampling techniques. For face validity, the two experts appointed were Malay language teachers with more than five years of teaching experience. To assess content validity, eight experts, including four professionals in measurement, evaluation, and global competency, and four field practitioners: teacher educators, and outstanding teachers. The instrument consists of 73 items with four constructs: self-awareness, global awareness, attitudes & values, and skills. The analysis involved Cohen’s Kappa for face validity, while content validity involved CVR and CVI. The results showed that face validity was (N=2, k=0.640), while for content validity, (N=8, CVI=0.95, and CVR=2 items refined). This instrument demonstrates strong validity as a measurement tool for the global competency level of Malaysian teachers. Further studies are recommended to be conducted: employing an advanced statistical analysis, like the Rasch Model, to enhance higher-quality items.